Importance of clinical and morphological correlations in diagnosing langerhans cell histiocytosis - Omayma SEB,; Fauzana K,; Aisyah MR,; Noraidah M,; Noor Hamidah Hussin, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Langerhans cell histiocytosis (LCH) is a clonal histiocytic disorder. The variable clinical manifestations from isolated bone lesion to multisystem disease can cause difficulties and delay in diagnosis. We report a 2 years and 8 months-old girl who presented with a 2 weeks history of persistent fever and weight loss associated with progressive abdominal distension. Physical examination revealed pallor, bilateral proptosis, seaborrheic dermatitis over the scalp and hepatosplenomegaly. Skull X-ray demonstrated multiple lytic lesions at the base and the skull vault. Bone marrow morphology showed numerous abnormal Langerhans cells (LCs) and foamy macrophages. The trephine immunohistochemistry (IHC) stains for CD1a, S-100 and CD68 were inconclusive. The diagnosis of multisystem Langerhans cell histiocytosis (MS-LCH) in this patient was based on the clinical presentation, radiological and morphological analysis. She subsequently received chemotherapy and currently she is on maintenance therapy with a good clinical response. LCH is a rare disease and although the IHC was inconclusive, the correlation of clinical, radiological and morphological data are essential for the diagnosis.